The Synthesis of 5,5-Disubstituted Piperidinones via a Reductive Amination–Lactamization Sequence: The Formal Synthesis of (±)-Quebrachamine - Grover, Huck K.; Kerr, Michael A. (Synlett, 2015)
A preliminary investigation into the prospect of a common synthetic intermediate for the synthesis of a variety of indole alkaloids has led to a synthesis of substituted piperidinones and the corresponding piperidines. These common natural product cores are accessed via a reductive amination–lactamization sequence of dimethyl 3-ethyl-3-formylpimelate. The synthetic utility of this initial study has been displayed in the formal synthesis of (±)-quebrachamine.
Keywords: natural product; alkaloid; quebrachamine; heterocycles; piperidine